Anxiolytic and antidepressant-like effects of Ferulago angulata essential oil in the scopolamine rat model of Alzheimer’s disease - Bağcı, Eyüp; Akbaba, Emel Aydın; Mihasan, Marius; Maniu, Calin; Hritcu, Lucian (My University, 2015)
Ferulago angulata subsp. carduchorum (Apiaceae) is a shrub indigenous to western Iran, Turkey and Iraq. In traditional medicine, F. angulata is recommended for treating digestive pains, haemorrhoids, snake bites, ulcers and as a sedative. The present study analysed the possible anxiolytic, antidepressant and antioxidant properties of F. angulata essential oil in a scopolamine-induced rat model of Alzheimer’s disease. The anxiolytic and antidepressant-like effects of F. angulata essential oil were studied using in vivo (elevated plus-maze and forced swimming tests) approaches. Also, the antioxidant activity in the amygdala was assessed using superoxide dismutase, glutathione peroxidase and catalase specific activities, the total content of the reduced glutathione, protein carbonyl and malondialdehyde levels. The scopolamine-treated rats exhibited the following: a decrease in the percentage of the time spent and the number of entries in the open armwithin the elevated plus-maze test and a decrease of swimming time and an increase of immobility time in the forced swimming test. Inhalation of F. angulata essential oil significantly exhibited anxiolytic and antidepressant-like effects and also antioxidant potential. Furthermore, in silico studies carried out by employing molecular docking experiments pointed to the existence of strong interactions of monoterpenes from F. angulata essential oil with anxiolytic and antidepressant effects with GABAA receptor. Our results suggest that the F. angulata essential oil inhalation ameliorates scopolamine-induced anxiety and depression by attenuation of the oxidative stress in the rat amygdala. Copyright © 2015 John Wiley & Sons, Ltd.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Ferulago angulata essential oil; Alzheimer’s disease; Anxiety; Depression; Oxidative stress